DEVELOPING A COMPREHENSIVE MODEL OF ORGANIZATIONAL EFFECTIVENESS REGARDING THE DIMENSIONS AND COMPONENTS OF KNOWLEDGE-BASED DECISION MAKING IN IRANIAN TAX ADMINISTRATION - Bonjar, Hamidreza; Salajegheh, Sanjar; Pourkiani, Masoud; Sayadi, Saeed (Revista Inclusiones, 2019)
This aim of the present study was introducing a comprehensive model of organizational effectiveness regarding the dimensions and components of knowledge-based decision making in Iranian tax administration. This study was mixed and applied in terms of design and purpose, respectively. This article included three sections. The first section addressed the background and the theoretical foundation related to the knowledge-based decision-making dimensions and components. The second section addressed the qualitative study using the grounded method. Finally, in the third section, the quantitative approach and modeling were considered based on a partial least squares approach. The statistical population of the article in the qualitative section included experts and elites of Iranian tax administration. Managers and specialists who had the required information for this article, using targeted sampling method, were selected to reach the theoretical saturation level; thus, finally, 50 people were interviewed. Triangulation and control methods were used to confirm the transcripts of the interviews as well as the interviewees to confirm and enhance the validity. The statistical population in the quantitative section included the general director, and the deputies, the directors of the staff, the directors of the Province of Tehran, the provincial governors, and deputy of provincial director, the elite experts, the executive experts, and senior experts of Iranian tax administration, which were totally 295 individuals.